Multi-Condition Temperature Field Simulation Analysis of Magnetorheological Grease Torsional Vibration Damper - Xiao, Zida; Hu, Hongsheng; Ouyang, Qing; Shan, Liyang; Su, Hongbo (Frontiers in Materials, 2022)
To reveal the transient temperature distribution pattern inside the magnetorheological grease (MRG) torsional vibration damper and explore the relationship between the current and the internal temperature of the device, the transient temperature simulation analysis of the MRG device was conducted in this paper. Firstly, a theoretical heat transfer model of MRG torsional vibration damper with dual heat source structural feature was established based on the Bingham constitutive model and the temperature-dependent viscosity characteristic of MRG. Then, the transient temperature field model of the MRG torsional vibration damper was developed by the finite element method, and the temperature field distribution and temperature-time variation characteristics of the MRG torsional vibration damper at 0A, 1A and 2A working conditions were analyzed, the effects of viscosity and slip factors on the temperature rise of the device were investigated. The simulation results show that the temperature rise of MRG in the working domain is the fastest, but gradual slowing of temperature rise rate. The magnitude and rate of temperature rise are maximum when the 1A current is applied to the torsional vibration damper. Finally, the current-temperature curve is obtained by fitting the simulation results. The results of the analysis reveal the internal temperature distribution and temperature rise characteristics of the torsional vibration damper, which provides a theoretical basis for the structural optimization and control strategy design of MRG torsional vibration damper considering temperature factor.